Finite element analysis of bolted joints - Loy, Tai Wei (2016)
This project aims to develop a standard design procedure for the contact analysis of bolted joints using finite element analysis (FEA). The developed procedure would be able to determine the stress distribution on the bolt & plate structure. The FEA program used for this study was ANSYS (academic version 15.0). The first step is to create a one bolt model and subsequent model will be created for the analysis problem. The results from the model will allow us to understand and predict how the structure support and resist imposed loads. The analyses will be performed with different parameters imposed, and stress distribution behavior can be studied. The basic knowledge of finite element analysis and ANSYS acquired through this project will lay the foundation for the future simulation work.